Censo nacional agropecuario 1960 (GOBIERNO DE ARGENTINA, 1964)
CONTENIDO : Neuquén, Río Negro, Salta, San Juan, San Luis, Santa Cruz, Santa Fe, Santiago del Estero, Tucumán, Tierra del Fuego, Islas Malvinas, Antártida e Islas del Atlántico Sur.